Un temprano abandono en los saladeros de Iulia Traducta (Baetica): el contexto cerámico tardoantonino del Parque de las Acacias - Bernal-Casasola, Darío; Jiménez-Camino Álvarez, Rafael; Retamosa-Gámez, José A. (Rei Cretariae Romanae Fautorum Acta, 2018)
Recent archaeological works conducted in 2015 at ancient Iulia Traducta (modern Algeciras, province of Cádiz in Andalusia, Spain), have unearthed new Roman fish salting plants active from the I to probably the V c. AD. One of the vats was abandoned in the third quarter of the II c. AD, probably as internal reforms inside one of the cetariae. A pottery context (250 individuals circa) has been studied in detail, including fine wares (mainly ARSW A, terra sigillata hispánica, thin walled pottery), common wares, lamps and amphorae (mainly local/regional garum vessels but also African, Italic, Galic and others). In this paper we present and discuss this so interesting and close pottery context, which offers a nice perspective of the economic dinamics in the Bay of Algeciras in Late-Antonine times.